The 419 syndrome in Nigeria : common practice - Bobbo, Sajo Dahiru (Abuja : Dikko Printing & Pub. Co., 2000)
The book elucidates the difficulties victims of deceits and 419 scam go through and the bad image these dastardly acts do to Nigerian image abroad.
oif 23/02/15
Loan
Keywords: Advance fee fraud -- Nigeria; Swindlers and swindling -- Nigeria; Corruption -- Nigeria; Fraud -- Nigeria. Bank fraud -- Nigeria